Silicon and gadolinium co-doped hydroxyapatite/PLGA scaffolds with osteoinductive and MRI dual functions - Xie, Shaodong; Guo, Min; Zeng, Deming; Luo, Hanwen; Zhong, Ping; Deng, Zixuan; Wang, Yu; Xu, Zhiqiang; Zhang, Peibiao (Frontiers in Bioengineering and Biotechnology, 2024)
An ideal bone repair scaffold should have dual functions of osteoinductive ability and in vivo imaging. In this study, simultaneous substitution of silicon (Si) and gadolinium (Gd) in hydroxyapatite (HA) as potential multifunctional of bone graft materials has been successfully developed. A series of HA nanoparticles (HA NPs) containing different Si and Gd doping amounts were prepared. The chemical structure and phase composition of the materials were analyzed by fourier transform infrared spectroscopy (FTIR) and X-Ray Diffraction (XRD). The microstructure, magnetic properties, surface potential and cytotoxicity of the materials were also analyzed. The magnetic resonance imaging (MRI) effect of Gd&Si-HA/poly(lactide-coglycolide)(Gd&Si-HA/PLGA) composite materials was evaluated. Osteogenic related genes expression, alkaline phosphatase (ALP) level and mineralization capacity of MC-3T3-E1 cultured on Gd&Si-HA/PLGA composite materials were also detected.1.5Gd&Si-HA@PLGA group showed good ability to promote osteogenic differentiation of cells. The MRI imaging effect of 1.5Gd&Si-HA@PLGA scaffold was very obviously. This HA material containing Si and Gd co-doping has a broad application prospect in the field of bone tissue engineering scaffolds in enhancing the osteoinductive ability and endowing MRI imaging ability of bone repair scaffolds.